Toward a contextual realism - Benoist, Jocelyn, 1968- (Harvard University Press, 2021)
"Esteemed philosopher Jocelyn Benoist argues for a renewed realism that takes seriously the context in which intention occurs. "What there is"-the traditional subject of metaphysics-can be determined only in context, Benoist contends, carving out a new path that rejects acontextual ontologies and approaches to the mind"--